Walter Harding (Historia, 2021)
In   a  secluded  portion   of  thf!' Military    Cemetery  at  Fort   Napier,  Pieter-maritzburg,   amidst the graves of numerous  British  soldiers  who  died  in  Natal,high  ranking  officers  and privates  alike,  lies  the  grave  of  Walter  Harding,  thelilst  r;esting  place  of  one  of  the  pi~neers  of   Natal,   and  one  who  made  alasting   mark   on  the  small   colony  during   a  large   portion   of  the  nineteenthcentury.rhis    article   i~  an   /!.ttempt  to   bring    Walter    Harding,   the   man,  intocorrect  perspective  in  relation  to  his  day,  and also  to  assess his  achievementsin  the  sphere  in  which  he  lived.Little   is  known  of  the  place  or  date  of  birth   of  Walter  Harding   and  thepresent, writer   has  searched  unavailingly    for  information. As  will   be  seenlater  there  was  some  confusion   at 1he  time  of  his   death  about  his   correctage.    But  it  is  certain  that  Walter   Harding   was  the  son  of  William    WalterHarding    (1782-1831)  and  Eliza  Herrick   (1793-1866) ,1William    Walter   Harding   purchased  an  ensigncy  in  the  20th  Regimentof  Foot  in;1800,   and  also  promotion   to  the  rank  of  Lieutenant   (.25-6-1803)and   Captain   (12-10-1809)   and  took  part   in  the  Allied    campaign   againstN~poleon,   doing   service  in'  Egypt   and  Spain.2IQ  November  1811  William   Harding   transferred  to  the  Cape Corps  andretired   from  the  army  in  June  1819  by  selling   his  commission.3   This  salecaused some comment  at the  time  and  it  has since come to  light  that  the  saleof  Harding's    commission  had  been  strongly  urged  by  the  then  Governor  atthe  Cape, Lord   Charles  Somerset!Soon  after  his   retirement   from   the   army,   William    Harding    obtainedt~e  post  of  Deputy  Landdrost-  at  Cradock,  but  he  soon relinquished   the  poston  account  of  bad  health.    He  thereafter  held  the  posts  of  Resident  Magis-trate,   Beaufort   West   (1-1-1828),    Justice   of   the   Peace  at   Graaff-Reinet(19-6-1828),   Resident  Magistrate,   Swellendam   (10-12-1828),   Justice  of  thePeace,  Swellendam   (28-2-1829)   and  Resident  Magistrate   and  Justice  of  thePeace  at  Uitenhage,  at  which   latter  place  he  died  on  27-3-183
Keywords: Fort Napier; Biography; Natal; Chief Justice; Harding, Walter; Military Cemeteries